Factors associated with the use of the Indonesia COVID-19 mobile app: What needs to be improved for the future personal mobile health app? - Yuyun Umniyatun; Izza Suraya; Emma Rachmawati; Mochamad Iqbal Nurmansyah (Public Health of Indonesia, 2023)
Background: Personal mobile health applications, including the COVID-19 mobile app, offer various benefits for enhancing the effectiveness of health programs.